4'-demethylnobiletin-rich fermented Citrus reticulata (ponkan) attenuated the disturbance in clock gene expression and locomotor activity rhythms caused by high-fat diet feeding. Issue 10 (3rd October 2022) - Haraguchi, Atsushi; Sato, Shuhei; Kusano, Shuichi; Ito, Kaede; Yamazaki, Tomohiro; Ryan, Conn; Sekiguchi, Masataka; Shibata, Shigenobu
ABSTRACT: Demethylnobiletins are nobiletin metabolites, with 4′-demethylnobiletin being the most abundant in the demethylated compounds upon feeding with nobiletin. Previous studies have repeatedly shown that demethylnobiletin has higher physiological activity than nobiletin; however, no studies have yet suggested that 4′-demethylnobiletin could affect biological rhythms. Therefore, in the present study, we analyzed the effects of fermented Citrus reticulata, containing a large amount of 4′-demethylnobiletin, on the locomotor activity level, locomotor activity rhythms under normal light-dark and constant-dark conditions, and peripheral clock rhythms. We demonstrated that fermented Citrus reticulata not only modified the changes in the locomotor activity rhythms caused by high-fat diet feeding in mice but also inhibited the phase shift of the peripheral clock rhythms caused by high-fat diet feeding. Taken together, the results of this study suggest that fermented Citrus reticulata could potentially be a new functional food that could help to maintain normal biological rhythms.